Implementation of Sharia Management in Islamic Mutual Fund Products - Rizki Ikha Riftiani; Diana Putri Lestari; Kharis Fadlullah Hana (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
Sharia management is one of the essential roles to determine the success of an Islamic financial institution. The existence of good and supportive regulations, healthy competition, increasing promotion to achieve an extensive market target make Mutual Fund Investment Services Products begin to show significant developments. One of them is the implementation of sharia management in BSM KC Kudus. The results showed that the performance of sharia management in BSM KC Kudus, Islamic mutual fund products, was implemented following Islamic sharia principles. The results of the discussion about the implementation of sharia management, which includes: performance of sharia management planning functions, namely (human resources, finance, and marketing) the second is the implementation of sharia management organizational functions, namely (the structure that is not following the contract) the third is an implementation of sharia management in the briefing function (employee personality in relationship with Allah SWT and humans) and implementation of sharia management oversight function (individual piety and employee control).